Alcohol consumption associated with suicidal ideation, and suicide attempts in substance users: A cross-sectional study of an addiction registry in western Iran - Vahid Farnia; Mahsa Mohebian; Omran Davarinejad; Denise A. Hien; Safora Salemi; Sara Hookari; Hafez Bajoghli; Bahareh Rahami (PLoS ONE, 2025)
Background Suicide is recognized as a major problem worldwide and is particularly prevalent among specific groups, including individuals with substance use disorders (SUDs). The present study aimed to investigate alcohol consumption as a risk factor for suicidal ideation and attempts among those with substance use disorders (SUDs) in western Iran. Methods This is a cross-sectional study, involving 1,112 individuals with SUDs who sought treatment at Farabi Hospital in Kermanshah, Iran, between the years 2019 and 2021. These participants were included in the study through a convenient sampling method as part of an interview-based assessment study. Results The participant’s average age was 37.97 years, and 982 were male (94.7%). Overall, 285 (27.5%) individuals had a history of suicide attempts, 316 (30.5%) individuals reported suicidal ideation, and 463 (41.6%) were alcohol users. In individuals who consumed alcohol, the prevalence of suicidal ideation (172 (37.2%) individuals), and a history of suicide attempts (156 (33.8%) individuals) was significantly higher compared to non-alcohol users. There was a statistically significant relationship between alcohol consumption and a history of suicide attempts (p < 0.05). The probability of suicide attempted in people with a history of alcohol consumption was 1.5 times, and in patients with a history of simultaneous substance use, it was 1.4 times that of other patients (all Ps < 0.05). Conclusion Our study results revealed that alcohol consumption among individuals with SUDs is associated with increased rates of suicidal ideation, attempts, and death. Therefore, clinicians should consider it as a separate suicide risk factor.